1976
DOI: 10.1007/bf00988660
|View full text |Cite
|
Sign up to set email alerts
|

Roentgen findings in fractures of the vertebral column in childhood Examination of 35 patients and its results

Abstract: In the past 10 years we examined 35 children with fractures of the spine. The most important cause was an injury by a fall from a tree or a climbing stage (23 cases). Traffic accidents or other direct trauma was the cause in 10 patients. Two children had tetanus, The ages of the children range from 2 to 12 years. Clinical symptoms may be diagnostic of vertebral trauma, but quite often symptoms are insignificant or atypical. We detected fractures in every vertebra of the thoracic and lumbar part of the spine. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…The most notable, the sub dental synchondrosis, is present in all children at age 3 and in 50% at age 5 [13,22,31,49,74,78,79]. It may per sist to the age of 11 [13] and radiographically may be mistaken for an odontoid fracture.…”
Section: Radiological Evaluationmentioning
confidence: 99%
See 3 more Smart Citations
“…The most notable, the sub dental synchondrosis, is present in all children at age 3 and in 50% at age 5 [13,22,31,49,74,78,79]. It may per sist to the age of 11 [13] and radiographically may be mistaken for an odontoid fracture.…”
Section: Radiological Evaluationmentioning
confidence: 99%
“…1). The development of ossification centers, chronology of epiphyseal closure, and details of spinal growth are dis cussed elsewhere [13,17,20,22,26,30,31], The vertebral bodies in the pediatric spine are wedge-shaped, and ver tebrae are primarily cartilaginous. The vertebrae will continue to grow during adolescence.…”
Section: Anatomical and Biomechanical Features Of The Developing Spinementioning
confidence: 99%
See 2 more Smart Citations
“…Gaca et al 9 performed a retrospective radiographic review looking at the occurrence and degree of wedging of the VB from T-10 to L-3 based on anterior/ posterior VB height measurements. Although the previously reported ratio of 0.95 was used as the cutoff for concern about compression fracture, 12 their study revealed that patients without spine injury can have an anterior/ posterior ratio of as low as 0.893. 15 All imaging modalities have their advantages and limitations.…”
mentioning
confidence: 99%